Pyridazine and its related compounds. Part 35 [1]: Synthesis, characterization and antimicrobial activity of some novel pyridazine and triazolopyridazine containing sulfonamides - Deeb, Ali AbdelHamid; El-Eraky, Wafaa Ibrahim; Mohamed, Sebaey Mahgoub (European Journal of Chemistry, 2015)
The present study describes the chemical synthesis and antimicrobial evaluation of some new pyridazine and triazolopyridazine derivatives. The structure assignments of the new compounds are based on chemical and spectroscopic evidences. The Study results showed that derivatives 6a, 6b, 6g and 6i have promising inhibitory activity against (Micrococcus luteus). Compound 6i has also noticeable inhibition activity against (Escherichia coli) and compound 3g show remarkable activity against (Candida albicans). Rest of compounds showed moderate to low activity against the examined microorganisms.